Activation properties of GAGA transcription factor. - Vaquero, A.; Blanch, M.; Espinás, M.L.; Bernués, J. (Biochimica et Biophysica Acta, 2008)
GAGA is a Drosophila transcription factor that has been involved in many nuclear activities. We present evidence that GAGA factor enhances transcription by stabilizing pre-initiation complex (PIC) and promoting reinitiation. Formation of PIC prior to GAGA addition prevents activation suggesting that GAGA is required early in the formation of activated complexes. GAGA stimulation of transcription can be attributed in part to a stabilization of PIC. All these properties depend on the GAGA C-terminal glutamine-rich domain and, in addition to other roles and together with previous data, support a role of GAGA as a transcription factor.